Impact of Seasonal Atmospheric Factors and Photoperiod on Floral Biology, Plant–Pollinator Interactions, and Plant Reproduction on Turnera ulmifolia L. (Passifloraceae) - Ujjwal Layek; Nandita Das; Arabinda Samanta; Prakash Karmakar (Biology)
Reproductive traits and plant–pollinator interactions largely depend on seasonal weather conditions, which are species-specific. Turnera ulmifolia is an ornamental plant distributed worldwide. There is little information about plant species’ reproductive ecology and environmental factors’ impact on it. Here, we aimed to examine the effects of seasonal atmospheric factors (e.g., temperature, light, relative humidity, rainfall) and photoperiod on flowering, interactions with flower visitors, and the reproductive success of Turnera ulmifolia in West Bengal, India. Flowering intensity peaked in hot summers and dropped in cold winters, correlating positively with temperature and humidity. Flower opening and closing occurred earlier on hot days, while flower longevity increased in winter, showing a negative correlation with temperature and humidity. Pollen and ovule production were lower in cold weather, positively linked to temperature and humidity. The self-compatible plant was moderately dependent on pollinators and had no pollination deficit in open conditions. Visitor abundance, richness, and diversity varied season-wise, with higher values during spring–summer. Based on pollinating agents, the plant showed multiple pollination modes (e.g., melittophily, myophily, myrmecophily, and psychophily). Effective pollinators were Amegilla zonata, Borbo cinnara, Halictus acrocephalus, Nomia (Curvinomia) strigata, and Tetragonula iridipennis. The fruit set (%) did not differ significantly season-wise, but the seed set remained higher in the hot days of summer than in cold winter. Therefore, it can be concluded that atmospheric factors and photoperiod significantly impact floral traits, plant–pollinator interactions, and plant reproduction.